Implementation of A Knowledge Management System to Increase Profit of the Company Case of PT. PE - Muhammad, Fahri; Sushandoyo, Dedy (Journal of Economics and Business UBS, 2023)
The IT industry has grown rapidly, resulting in fierce competition among enterprises. System integrators, such as PT. PE, confronts stiff competition, especially when serving government clients. However, profits at PT. PE have fallen during the last three years. The underlying cause of this problem has been identified through analysis using fishbone and cause diagrams as a lack of effective knowledge management within the company. This study aims to address two key questions: firstly, what is the knowledge management system that should be proposed to PT. PE to increase their profit? Secondly, what is the implementation plan of the proposed knowledge management system? A qualitative research method was used to study these questions. Data was gathered through interviews with important stakeholders such as the CEO, project managers (PM), and administrative employees. Observations were also done within the operations team. The data was collected from January through April 2023. The data analysis found nine sub-causes that contributed to the observed problem. These sub-causes include a lack of knowledge management understanding, disparities in employee knowledge levels, a lack of a platform for knowledge sharing, limited access to training and employee development programs, ineffective document storage, a lack of vendor and client databases, a lack of processes for converting tacit knowledge into explicit knowledge, a lack of a learning culture, and an overreliance on third parties. Several solutions based on the SECI (Socialization, Externalization, Combination, and Internalization) and People frameworks, procedures, and technologies are presented to overcome these difficulties. Ptalk, Pdoc, and Ptraining are among the knowledge management programs that PT. PE plans to implement. The implementation procedure is set to start in September 2023 and end in September 2024. Following deployment, an evaluation of the effectiveness of the knowledge management activities will be done, and appropriate modifications will be made for future enhancement. PE intends to reduce the highlighted issues and increase profitability by building a comprehensive knowledge management system. The suggested system will improve staff growth, expedite document storage, create databases for vendors and clients, build a learning culture, and eliminate reliance on third parties. PT. PE expects these steps to have a positive influence on their financial performance and long-term prosperity. Finally, this study underlines the significance of knowledge management for system integrator organizations such as PT. PE. The problems discovered in PT. PE's knowledge management processes have had a significant impact on its profitability. PT. PE, on the other hand, hopes to overcome these issues, improve their knowledge management processes, and, eventually, increase their profitability and competitive position in the IT market, through the offered solutions and implementation plan. In conclusion, this study emphasizes the crucial importance of knowledge management in the success of system integrator firms. The issues revealed in PT. PE's knowledge management methods have had a negative impact on its profitability. However, with the offered solutions and implementation plan, PT. PE hopes to overcome these problems, improve their knowledge management procedures, and ultimately increase their profitability and competitive position in the IT industry. This study contributes to the understanding of successful methods that might drive success for system integrator organizations in a highly competitive industry by emphasizing the relevance of knowledge management.